Concept Mastery and Mathematical Problem Solving Ability of High School Students in Uniform Motion in a Straight Line Materials (GLBB) - Dua Riong, Maria Bernadetha; Ahmadi, Farid; Supriyadi, Supriyadi (Journal of Innovative Science Education, 2022)
This study aims to describe the pattern of the relationship between students concept mastery and mathematical problem-solving ability in GLBB material. This is qualitative associative/constructive research. This investigation was conducted with grade X MIA2 students at SMAN 1 Nita. This study's instrument included a test of concept mastery and mathematical problem-solving ability, documentation of student answer sheets, and unstructured interviews. The technique for data analysis consisted of five stages: data collection, description of raw data, data reduction, data categorization, and construction of category relationships. The findings revealed a reciprocal relationship between concept mastery and mathematical problem-solving ability. In addressing physics problems, mastery of concepts and mathematical problem-solving ability play mutually reinforcing roles. The level of concept mastery of students increases with their problem-solving abilities, and vice versa: the higher the level of conceptual mastery, the greater the mathematical problem-solving abilities. The results showed that there was a semantic congruence between issue solving using the Polya step indicator and problem solving at the levels of analyzing (C4), evaluating (C5), and creating (C6). Keywords : GLBB, Concept Mastery, Mathematical Problem Solving Ability